Opportunities for Reference Services after Covid-19. Issue 3 (13th May 2021) - Flierl, Michael
Abstract: There is something to be learned from how academic library reference services adapted to providing accurate and timely information to students, faculty, staff, and other users during a global pandemic. In this spirit I present, in increasing order of importance, three specific opportunities for reference services in a post Covid-19 world: evolution in technology, distributed staffing models, and measuring efficacy against student learning and success. Most importantly, reference services ought to adapt its core mission to one focused on student learning and success given the likely financial realities academia and academic libraries will face in a post Covid-19 environment.